What makes 'aespa', the first metaverse girl group in the K-pop universe, succeed in the global entertainment industry? - Minju Jeong; Seongcheol Kim (International Telecommunications Society (ITS), 2023)
An illustrative example of technological advancement in the K-pop industry is SM Entertainment's metaverse girl group, aespa. Aespa, including four virtual members and four real-world members, distinguishes itself by adopting a metaverse-focused worldview and integrating virtual technology. By incorporating technology into their idol concept and delivering a distinctive "metaverse girl group" experience, aespa endeavors to set itself apart from other idol groups. Prior research in the realm of K-pop and idols has predominantly focused on success factors, the idols' working environment, and fashion trends, placing greater emphasis on environmental and contextual elements rather than the individual characteristics and strategies of specific idols. This study aims to investigate the success factors driving aespa's accomplishments in the global entertainment industry. We employ actor-network theory, which recognizes not only humans but also non-human entities as active participants within networks. This theoretical framework is deemed suitable for elucidating intricate social phenomena. This study utilizes actor-network theory as a analytical framework to investigate the implementation of new technologies in the K-pop industry. To achieve this, ten experts from the K-pop industry participated in the interviews. This study employs a case study approach to comprehensively analyze the dynamics and interactions within the network. Specifically, the case study centers around aespa, a metaverse K-pop girl group that achieved remarkable success during the COVID-19 pandemic. The findings of this study indicate that the global success of aespa was significantly influenced by the roles of A&R and executive producer prior to their debut. Furthermore, subsequent to their debut, technology, social networking services (SNS), and portals emerged as critical determinants. Moreover, the individual ability, appearance, personality of the idol and the agency's involvement played pivotal roles both before and after the debut stage. This study has contributed significant insights by applying Actor-Network Theory (ANT) to the idol industry. It highlights the important factors that K-pop idols need to consider for global industry expansion. The use of ANT provides a valuable framework for understanding the complex dynamics and interactions within the industry, shedding light on the key considerations for successful global ventures in the K-pop idol market.
Keywords: 330; K-pop; Success Factors; Actor-Network Theory; Metaverse; Aespa; Technology; Virtual Idol